In Silico Detection of Virulence Gene Homologues in the Human Pathogen Sphingomonas Spp. (January 2014) - Saeb, Amr T. M.; David, Satish Kumar; Al-Brahim, Hissa
There is an ongoing debate about the clinical significance of Sphingomonas paucimobilis as a virulent bacterial pathogen. In the present study, we investigated the presence of different virulence factors and genes in Sphingomonas bacteria. We utilized phylogenetic, comparative genomics and bioinformatics analysis to investigate the potentiality of Sphingomonas bacteria as virulent pathogenic bacteria. The 16S ribosomal RNA gene (16S rDNA) phylogenetic tree showed that the closest bacterial taxon to Sphingomonas is Brucella with a bootstrap value of 87 followed by Helicobacter, Campylobacter, Pseudomonas, and then Legionella. Sphingomonas shared no virulence factors with Helicobacter or Campylobacter, despite their close phylogenic relationship. In spite of the phylogenetic divergence between Sphingomonas and Pseudomonas, they shared many major virulence factors, such as adherence, antiphagocytosis, iron uptake, proteases, and quorum sensing. In conclusion, Sphingomonas spp. contains several major virulence factors resembling Pseudomonas sp., Legionella sp., Brucella sp., and Bordetella sp. virulence factors. Similarity of virulence factors did not match phylogenetic relationships. These findings suggest horizontal gene transfer of virulence factors rather than sharing a common pathogenic ancestor. Sphingomonas spp. is potential virulent bacterial pathogen.